Path to the pros : how major league soccer is revolutionizing youth player development in the United States - Cocco, Adam R.; Spencer, Tyler C. (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Traditionally, major league professional sport organizations in the United States are not active participants in the youth player development process. They instead wait to acquire amateur talent through league-wide drafts. However, beginning in 2007, Major League Soccer (MLS) and the United States Soccer Federation (USSF) partnered to initiate a system whereby professional soccer teams in the United States develop youth soccer players through internal development academies. This marks a definitive change to the standard youth player development process in the United States and offers numerous benefits to MLS teams and the ongoing growth of soccer in this country overall. This case study asks readers to critically assess traditional youth development practices in the United States and compare them to the development academy model offered by MLS organizations. The following aspects of youth player development in the United States provide a basis for this assessment: (a) player skill development, (b) the pay-to-play structure commonly employed in youth sport participation, and (c) the integration of educational principles along with player development. Although there is no perfect youth player development model, questions arise as to whether the MLS development model would offer similar benefits if adopted by other major professional sport leagues in the United States.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Major League Soccer (Organization); United States Soccer Federation; Soccer -- Vocational guidance -- United States -- Case studies; Soccer for children -- Training -- United States -- Case studies